Introduction of soybean glycinin gene into rice (Oryza sativa L.) with Agrobacterium-mediated transformation - ZHANG Xian-yin; XUE Qing-zhong (浙江大学学报. 农业与生命科学版)
Based on the previous work of cloning of upstream sequence of a rice glutelin gene Gt1, an Agrobacterium binary vector based on pCAMBIA1301 was reconstructed with a soybean glycinin gene-directed by the tissue specific promoter, and was used in rice transfomation. The target gene was successfully introduced into calli of an early japonica rice variety with Agrobacterium-mediated transformation and several transgenic plants were obtained. PCR analysis of the transformed plants and Hyg resistance tests of To seeds showed the integration of the target gene and its stable inheritance to offsprings,